The power of media narratives: Al Jazeera's influence on international solidarity for Palestine - Wahdah Salsabillah; Arie Kusuma Paksi (Master of Communication Science Program, Universitas Diponegoro, 2025)
The media plays an important role in shaping public opinion and mobilizing global solidarity in the context of conflict. This study examines how Al Jazeera constructs an emotional narrative related to the Palestinian-Israeli conflict through its reporting on its official website to encourage global support. This study uses Robert Entman (1993) framing theory and Manuel Castells (2012) concept of global solidarity, with a descriptive qualitative approach. The main data were collected from 260 Al Jazeera news articles and 100 public comments from 10 YouTube videos related to the conflict, analyzed between 2023 and 2024. The articles were analyzed using NVivo 12 software to identify three framing strategies: (1) Call to Action, (2) Focus on Victims, and (3) Narrative of Injustice. Meanwhile, YouTube comments were analyzed using three classifications, covering expressions of: (1) Empathy, (2) Moral Outrage, and (3) Support for Palestine. The results show that Al Jazeera's framing was able to construct a narrative that was emotionally touching and encouraged cross-border solidarity. The public response showed a strong emotional impact on the narrative constructed, indicating the potential of digital media as a tool for transnational advocacy. This study concludes that the media not only conveys information but also plays an active role in shaping global public opinion through strategic and humanistic narratives. This research recommends further research into the long-term impact of media narratives on public opinion and international policies related to the Palestine-Israel conflict.